Suppression of Recombination Losses in Polymer:Nonfullerene Acceptor Organic Solar Cells due to Aggregation Dependence of Acceptor Electron Affinity. Issue 27 (12th June 2019) - Cha, Hyojung; Fish, George; Luke, Joel; Alraddadi, Ahmad; Lee, Hyun Hwi; Zhang, Weimin; Dong, Yifan; Limbu, Saurav; Wadsworth, Andrew; Maria, Iuliana P.; Francàs, Laia; Sou, Hou Lon; et al.
Abstract: Here, it is investigated whether an energetic cascade between mixed and pure regions assists in suppressing recombination losses in non‐fullerene acceptor (NFA)‐based organic solar cells. The impact of polymer‐NFA blend composition upon morphology, energetics, charge carrier recombination kinetics, and photocurrent properties are studied. By changing film composition, morphological structures are varied from consisting of highly intermixed polymer‐NFA phases to consisting of both intermixed and pure phase. Cyclic voltammetry is employed to investigate the impact of blend morphology upon NFA lowest unoccupied molecular orbital (LUMO) level energetics. Transient absorption spectroscopy reveals the importance of an energetic cascade between mixed and pure phases in the electron–hole dynamics in order to well separate spatially localized electron–hole pairs. Raman spectroscopy is used to investigate the origin of energetic shift of NFA LUMO levels. It appears that the increase in NFA electron affinity in pure phases relative to mixed phases is correlated with a transition from a relatively planar backbone structure of NFA in pure, aggregated phases, to a more twisted structure in molecularly mixed phases. The studies focus on addressing whether aggregation‐dependent acceptor LUMO level energetics are a general design requirement for both fullerene and NFAs, and quantifying the magnitude, origin, and impact of such energetic shifts upon device performance. Abstract : An energetic cascade between mixed and pure regions assists in suppressing recombination losses in nonfullerene acceptor (NFA)‐based organic solar cells. The impact of polymer–NFA blend composition upon film morphology, energetics, charge carrier recombination kinetics, and photocurrent properties is studied.